The Effect of Manganese, Chromium and Boron into the Hardness and Microstructure of Steel Shot - Nurjaman, Fajar (Teknologi Indonesia, 2012)
The objectives of this experiment were to investigate the effect of alloying elements, such as manganese, chromium, and boron, and also the effect of heat treatment into the hardness and microstructure of steel shot. Inthis experiment, a steel shot containing of 0.5?0.8% C was produced. The manufacture of steel shot was carried out by using the injection-pressurized water method. The raw materials, such as steel scrap and alloying elements were melted in an induction furnace. The round shape steel or steel shot with 0.5?3.2 mm in diameter was obtained by injecting the molten steel, which was fl owed from induction furnace into a distributor (pan crucible), by 1.1 atmosphere of pressurized water using a nozzle, and then the steel shot was splashed down into a tank containing water for cooling process. The dimension of pan crucible was in the form of cylinder tube with 300 mm in diameter and 130 mm in length, containing of 107 holes, with 10 mm in diameter for each hole. Some tests were conductedinto steel shot material, there were the hardness testing by using a Rockwell hardness tester, and the microstructure analysis by using an optical microscope. The addition of manganese, chromium, and boron into steel shot caused the hardness value of steel shot signifi cantly increased, 57 HRC for 3.6% Cr and 55 HRC for 2.3% Mn?1.8% Cr?2% B. The heat treatment process, by tempering at temperature 250oC for 5 minutes, produced fi nely martensite on its microstructure with 58 HRC (the hardness of as-manufactured steel shot was 55 HRC).